Nepal’s National Security in Changing Political Circumstances - Bagale, Sarmila (DMC Journal, 2023)
This article explores the several security challenges faced by small and landlocked countries which seem to be harmful for peace, prosperity, security and development. Small and landlocked countries, like Nepal, in the world are experiencing different security challenges at present in the backdrop of different political power. The national security in twenty first century is meant for peace, prosperity and economic progress and development. In the changing dynamics of Nepal, especially after the promulgation of the Constitution in 2015, the security issue has been a major concern for political stability and international relations. Though the security issue has a very long history, since the beginning of human civilization it was important, its goal is not ended yet. Nonetheless, the internal and external dynamics of national security have been shifted in the changing contexts of regional, and global political power. It has diverse sensitivity in different circumstances of political regime. The classical agro-based state-constructed security is relocated into human-centric notion for peace, stability and development. Contrary the small and landlocked states are always in threat in different ways which is undoubtedly different things to different people. The sense of national security in the academia involves mitigation of physical threat and psychological fear. As a result, the cherished values collapsed and affect the conditions of peace, stability and development.